2005
DOI: 10.1084/jem.20050749
|View full text |Cite
|
Sign up to set email alerts
|

A novel glyco-conjugate vaccine against fungal pathogens

Abstract: To generate a vaccine to protect against a variety of human pathogenic fungi, we conjugated laminarin (Lam), a well-characterized but poorly immunogenic β-glucan preparation from the brown alga Laminaria digitata, with the diphtheria toxoid CRM197, a carrier protein used in some glyco-conjugate bacterial vaccines. This Lam-CRM conjugate proved to be immunogenic and protective as immunoprophylactic vaccine against both systemic and mucosal (vaginal) infections by Candida albicans. Protection probably was mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
366
3
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(393 citation statements)
references
References 44 publications
8
366
3
9
Order By: Relevance
“…Interestingly, only a minimal rise in antibody to b-glucan was found, suggestive that antibodies play a minimal role in protection (Clemons et al, 2014b). The latter is in opposition to the studies using laminarin conjugated to diphtheria toxoid, which suggested antibody directed against b-glucan was a major mechanism of protection against multiple fungal infections ( Torosantucci et al, 2005Torosantucci et al, , 2009). As we noted previously, induction of the various pro-inflammatory cytokines and chemokines is suggestive of a priming of an active innate immune response, whereas increases in IFNc and IL-17 suggest an induction of a cell-mediated immune response (Zelante et al, 2009;Clemons et al, 2014b;Whibley & Gaffen, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, only a minimal rise in antibody to b-glucan was found, suggestive that antibodies play a minimal role in protection (Clemons et al, 2014b). The latter is in opposition to the studies using laminarin conjugated to diphtheria toxoid, which suggested antibody directed against b-glucan was a major mechanism of protection against multiple fungal infections ( Torosantucci et al, 2005Torosantucci et al, , 2009). As we noted previously, induction of the various pro-inflammatory cytokines and chemokines is suggestive of a priming of an active innate immune response, whereas increases in IFNc and IL-17 suggest an induction of a cell-mediated immune response (Zelante et al, 2009;Clemons et al, 2014b;Whibley & Gaffen, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…And, although galectin-3 is known to participate in phagocytosis of microbial PAMPcoated beads (29), we observed the fungicidal effect of galectin-3 in the absence of macrophages or other cells of the mammalian immune system. The mechanism of galectin-3 fungal death is not clear at this point; however, recent studies of oligosaccharidebased vaccines for C. albicans demonstrated a direct fungicidal activity for Abs that recognize ␤-glucans in the yeast cell wall (57). These observations suggest that cross-linking of oligosaccharide components in the fungal cell wall, either by multivalent galectins such as galectin-3 or by Abs, can directly trigger death.…”
Section: Discussionmentioning
confidence: 99%
“…One uses killed S. cerevisiae to direct immune cells to recognize common fungal wall polysaccharides including glucans and mannans (Liu et al 2011a). Another universal vaccine design uses b-glucans conjugated to an inactivated version of diphtheria toxin to elicit responses against different pathogenic fungi (Torosantucci et al 2005). These aforementioned studies are described at greater detail below.…”
Section: Vaccinesmentioning
confidence: 99%
“…Protection from mortality was at least partially conferred by elicited antibodies, as adoptive transfer of antisera from immunized animals also protected mice from a lethal inoculum of intravenously administered C. neoformans (Devi 1996). Torosantucci et al (2005) have conjugated laminarin, a b-glucan polysaccharide derived from brown algae, to inactivated diphtheria toxin (CRM) to create a universal fungal vaccine. This conjugate, injected with complete Freund's adjuvant (CFA) subcutaneously, protected 70% and 80% of CD2F1 mice from invasive candidiasis and aspergillosis, respectively, whereas 20%-30% of mice given CFA or CRM alone survived either infection.…”
Section: Conjugate Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation